1999
DOI: 10.1001/archsurg.134.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Does the Face Protect the Brain?

Abstract: Background: The relationship between facial fractures and traumatic brain injury is controversial. Some studies show an increased risk of brain injury with the presence of facial fractures while others claim that facial fractures protect against brain injury. Objective: To examine the association between facial fractures and traumatic brain injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(21 citation statements)
references
References 4 publications
5
16
0
Order By: Relevance
“…The majority of articles that examined TBI and all articles on children and youth with TBI included ICD-10 codes S02.0, S02.1, S02.3, S02.7, S02.8, and S02.9 in their case definitions. Many studies have identified TBI among individuals with facial fractures [ 11 , 12 , 46 , 67 - 76 ] as well as an increased risk for fractures of the orbital floor (S02.3) [ 68 , 71 , 75 ], malar maxillary bones (S02.4) [ 68 , 71 ], and the mandible (S02.6) [ 71 , 74 ]. Previous research has shown that brain injury is one of the most common concomitant injuries among children with mandibular and mid-facial fractures [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of articles that examined TBI and all articles on children and youth with TBI included ICD-10 codes S02.0, S02.1, S02.3, S02.7, S02.8, and S02.9 in their case definitions. Many studies have identified TBI among individuals with facial fractures [ 11 , 12 , 46 , 67 - 76 ] as well as an increased risk for fractures of the orbital floor (S02.3) [ 68 , 71 , 75 ], malar maxillary bones (S02.4) [ 68 , 71 ], and the mandible (S02.6) [ 71 , 74 ]. Previous research has shown that brain injury is one of the most common concomitant injuries among children with mandibular and mid-facial fractures [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrate that the rate of concomitant head injuries in cases of facial fracture is as high as 50- 80 %- depending on the location of the fracture [4]. While intracranial injuries occur most often in cases of fractures of the bones of the upper face and maxilla, they are less frequently associated with lesions of the mandible [4–6]. Besides involvement of the head, other concomitant injuries include the cervical spine and other body parts (Figs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the S02 code for fracture of the orbital floor (S02.3) is included in the definition used in Ontario [20-22]. The inclusion of the code S02.3 was based on three separate studies: first a case-control study of those injured in a bicycle accident found that those with brain injuries had 24.4 times the odds of also having an orbital fracture compared to those without a brain injury [20]; a study of those hospitalized for a motorcycle collision found that 70.2% of those with a orbital facial fracture also sustained a brain injury [21]; finally, a retrospective data study using a trauma database found that more people had TBI among those with facial fracture compared to those without facial fracture (p < 0.0010) [22]. (See table 5 for more information).…”
Section: Discussionmentioning
confidence: 99%